2014
DOI: 10.1080/01634372.2014.919977
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Korean Immigrant Elders Living in Canada and the United States: A Comparative Study

Abstract: Korean immigrant elders in North America experience a high level of depression. This study explored the correlates of depression among a sample of 245 Korean immigrant elders living in metropolitan cities in Canada (n = 128) and a southwestern state in the United States (n = 117), using a stress-coping framework. Results revealed discrepancies between the 2 subgroups. Years since immigration and number of health concerns were positively associated, and English proficiency was negatively associated with depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Older Korean immigrants with severe neuroticism are more likely to experience higher levels of depression. This result is consistent with previous studies [ 26 , 6 , 7 ]. It is defined that neuroticism is a fundamental personality trait characterized by anxiety, worry, and excessive stress [ 5 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Older Korean immigrants with severe neuroticism are more likely to experience higher levels of depression. This result is consistent with previous studies [ 26 , 6 , 7 ]. It is defined that neuroticism is a fundamental personality trait characterized by anxiety, worry, and excessive stress [ 5 ].…”
Section: Discussionsupporting
confidence: 94%
“…Neuroticism is a personality trait characterized by worry, moodiness, and nervousness [ 5 ]. Higher levels of neuroticism have been positively associated with depressive symptoms among the general population of older adults in the U.S. [ 4 , 6 , 7 ]. Hayward and colleagues [ 4 ] found that decreasing neuroticism can result in an improvement of depression in their study of 112 older adults with major depression.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants who migrate in mid-adulthood or later may be particularly slow to adapt to a new society ( W. Kim, Kang, & Kim, 2015 ). Older immigrants are more likely to have depression due to limited English proficiency, cultural adjustment difficulties, stresses from changes in social status, and intergenerational differences in acculturation, breakdown of traditional support systems, financial strain, racial prejudice and discrimination ( G. Kim, Jang, Chiriboga, Ma, & Schonfeld, 2010 ; Park & Roh, 2013 ; Zhang, Fang, Wu, & Wieczorek, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Older immigrants are more likely to have depression due to limited English proficiency, cultural adjustment difficulties, stresses from changes in social status, and intergenerational differences in acculturation, breakdown of traditional support systems, financial strain, racial prejudice and discrimination ( G. Kim, Jang, Chiriboga, Ma, & Schonfeld, 2010 ; Park & Roh, 2013 ; Zhang, Fang, Wu, & Wieczorek, 2013 ). In addition, older adults are more likely to encounter significant life changes, such as deteriorating health, reduced financial ability, or the loss of a loved partner, resulting in a higher risk of depression ( W. Kim et al, 2015 ). Late-life depression may reduce the quality of life, worsen physical functioning and cognition, and increase health care costs ( Cotrena, Branco, Kochhann, Shansis, & Fonseca, 2016 ; Steensma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation